Are haematological and biochemical properties of freshwater spotted snakehead Channa punctata (Bloch, 1793) season and sex dependent? - Minakshi Singh; Ankur Kashyap; Mohammad Serajuddin (Journal of Fisheries, 2020)
Freshwater murrel, Channa punctata commonly known as “spotted snakehead” is a popular fish because of its taste and price. Haematological and biochemical profile of fish helps in understanding the fish health and play an important role in fisheries management. The present work was carried out to determine season (summer, monsoon and winter) and sex dependent variations in the blood profile of C. punctata. Haematological [red blood cell counts (RBC), packed cell volume (PCV) and haemoglobin (Hb)] and serum biochemical parameters [blood glucose, total protein, cholesterol, triglyceride (Tg), low density lipoprotein (LDL), very low density lipoprotein (VLDL), high density lipoprotein (HDL), serum calcium levels] of C. punctata were analysed which varied significantly with seasons (p < 0.05). The level of glucose, total protein, Tg, VLDL, RBC, Hb and PCV was low during monsoon season because of the growth and development of gonads compared to the summer and winter season. The level of cholesterol and LDL was high during monsoon. However, haematological and biochemical parameters were not sex dependent. The seasonal haematological and biochemical variations in the fish were mainly due to the physiological acclimatisation of the fish to variations in the environmental condition and feeding regime.